Pengaruh Jenis Mulsa terhadap Pertumbuhan dan Produksi Kemangi (Ocimum basillicum) (Jurnal Ilmiah Teknologi Pertanian Agrotechno, 2021)
Basil plants (Ocimum basillicum) is medicinal plants, can produce essential oils, and consume as a food ingredient. However, the production of Basil plants is still low due to the growth of weeds that is not easy to be controlled, causing market demand to still not be fulfilled. One of the measures to increase the yield is to suppress weed growth using mulch on cultivation. The purpose of this study was to determine the effect various types of mulch on growth and production of Basil plants. The research design used was a Randomized Block Design (RAK) with 4 types of treatment which was repeated 6 times. Observed parameters were plant height, number of leaves, number of branches, plant fresh weight, and also environmental factors, namely soil moisture and soil pH. Analysis of Variance applied to calculate the effect of treatments and DMRT test at ? =5% was applied to determine the significancy of treatment. The results showed that rice straw mulch had a significant effect on plant height, number of leaves, number of branches, fresh weight and soil pH.
Keywords: basil; mulch; growth; yield